HEALTH COMMUNICATION LITERACY IN EMPOWERMENT OF COMMUNITY HEALTH IN INDONESIAN TOURISM AREA - K. Y.S. Putri; Vera Wijayanti Sutjipto; Wiratri Anindhita; Nada Arina Romli; Yesi Andriani; Diva Rheva Deianeira (Institute of Research and Community Outreach - Petra Christian University, 2022)
The pandemic has made people really need health information in order to maintain the health of themselves and their families. Previous research has discussed a lot about maintaining health through new media. The formulation of the research problem is whether there is an influence of health communication literacy on people's attitudes in maintaining health in tourist areas in Indonesia. The purpose of the study was to determine the literacy of health communication in empowering public health in tourist areas. The concept used in the study is literacy of health communication and public attitudes in maintaining health in the pandemic, 2021. The research method used is quantitative by distributing questionnaires to respondents. The results of the research are descriptively all variables in the study are positive. This has an impact on the next research process, namely that there is a strong influence of health communication literacy in health empowerment. This states that the alternative hypothesis is accepted by the study and the null hypothesis is rejected. Media content, skills in using new media and understanding of health information together have a strong influence on people's attitudes in maintaining health in tourist areas in Indonesia in 2021. People in tourist areas are also very concerned about mutual health. Because they are very aware that the economic condition is very dependent on tourism. Therefore, if the entire population in the tourist area is healthy, then tourism in the area will be visited by many local and foreign tourists. Research suggestion is that this research can be developed by elaborating other knowledge studies, and elaborating other methods.